BIODIVERSIDADE DE DROSOFILÍDEOS E VARIABILIDADE GENÉTICA DE DROSOPHILA ANTONIETAE EM FRAGMENTOS DE HABITAT NO CURSO MÉDIO DA BACIA DOS RIOS PARANÁ-URUGUAI - Simão, Daiane Priscila (2010)
This work aimed to evaluate the composition of the Drosophilidae fauna in an area of Araucaria forest in order to obtain data to understand the effects of fragmentation of this biome on the biodiversity of this group of insects. In addition, we intend to infer aspects of ecological and historical events that occurred in a cactophilic species of the D. buzzatii cluster, D. antonietae, which could shed light to better understand how speciation occurs in the tropical and subtropical regions. The data on species occurrence, species richness, vertical and horizontal beta diversity resulted in a high contribution to comprehend the Drosophilidae community dynamics on fragmented areas of Araucaria forest in the Guarapuava region, and will serve as a reference for future projects regarding conservation of this biome biodiversity, which is under intense process of degradation. For D. antonietae, low genetic differentiation among populations was observed in the Regional Analysis, with no significant correlation between genetic and physical distances. In the Macrogeographical Analysis, a moderate genetic differentiation was found and the genetic distance index was representative of the moderate differentiation. The genetic distance was more similar between the populations located in the higher and lower portion of the basin, and the populations located in the middle portion were more distant. The correlation between genetic and physical distances, analysed through the Mantel test, was also not significant, indicating no correlation between them. Thus, homogeneity and high degree of polymorphism in natural populations of D. antonietae must be due to maintenance of shared ancestral polymorphisms, and the gene flow should have acted during the populations expansions and retractions that have occurred in the evolutionary history of this species.